Recurrent non immune hydrops fetalis: a case report - Nigam, Shipra; Shankar, Kundavi; Varma, Thankam Rana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Recurrent non-immune fetal hydrops (NIHF) is a known but rare disease. We report a case of recurrent fetal hydrops in a multipara with no significant surgical or medical history. She presented for a preconceptional counselling with a background history of having two previous pregnancies affected by hydrops. Both the affected pregnancies resulted in mid trimester pregnancy termination. Detailed evaluation of the couple was done in our hospital before planning the third pregnancy. No obvious cause of recurrent hydrops was found. She conceived spontaneously and finally delivered a healthy baby. This case highlights the fact that thorough investigation is essential in case of hydrops fetalis so that further pregnancies are not affected.